Quantification Of Greenhouse Gas Emissions in a Cement Company and System Dynamics Modeling Toward Carbon Neutral - Harijanto, Rizky Tazkia Arethusya; Dewi, Kania; Wahyudi, Arifuddin (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
The cement industry is one of the sectors that produces carbon dioxide (CO2) emissions due to its raw material processing and energy requirements. CO2, as a greenhouse gas (GHG) emission, contributes to global warming, leading to environmental, health, and economic losses. To address these issues, Indonesia is committed to reducing GHG emissions in the industrial sector by 2050. To effectively plan for the reduction of GHG emissions generated by companies, this study aims to quantify emissions from a cement company, representing the cement industry in Indonesia, to understand the current state of the company's carbon footprint and identify feasible mitigation measures. The cement industry utilizes a GHG quantification system to calculate emissions from raw material processing, thermal energy consumption, and electricity purchases. The calculation results from a cement company are used for system dynamics modeling with Vensim PLE software for the period from 2021 to 2050, under business-as-usual (BAU) conditions with various emission reduction strategies. The results show that GHG emissions under BAU conditions with emission reduction strategies do not achieve carbon neutrality by 2050. More intensive adoption of decarbonization technologies, research on process optimization, and government policies such as carbon taxes and carbon trading are required to achieve carbon neutral goals.